Оценка современного состояния флоры санитарно-защитной зоны проектируемого Шимановского горно-обогатительного комбината и сопредельной территории (Днепропетровская обл.) - Кучеревский, В.В.; Баранец, Н.А.; Сиренко, Т.В.; Шоль, Г.Н. (Промышленная ботаника, 2014)
Цель настоящей работы заключалась в изучении современного состояния флоры на территории, отводимой под строительство Шимановского ГОКа и в оценке влияния последнего на флору региона. Представлені результати вивчення антропогенно трансформованних флор санітарно-захисної зони запроектованого Шиманівського гірничо-збагачувального комбінату (ГЗК) у м. Кривий Ріг і суміжної території. Вивчений видовий склад флор напівприродних екосистем, агроекосистем і техногенних екосистем. Проведені систематичний, екологічний, географічний, біоморфний, еколого-ценотичний аналізи виділених флор. Визначена созологічна цінність флори санітарно-захисної зони і прилеглої до неї території балки Зеленої. Зроблений прогноз впливу ГЗК на флору та рослинність. The paper presents data obtained in the course of studying of anthropogenic transformed floras of the sanitary-protected zone of the prospective Shymanovsky ore-mining and processing combine (OMPC) in Krivoy Rog and adjacent territory. Specific structures of flora of semi-natural ecosystems, agroecosystems and technogenic ecosystems were studied. We carried out the systematic, ecological, geographical, biomorphic, ecologo-cenotical analyses of these distinguishable floras. We estimated sozological importance of flora in a sanitary-protection zone and adjoining area in Zelenaya Balka (gully). Basing on the study a forecast of OMPC influence on flora and vegetation has been made.